Tingkat Pemahaman Calon Guru Terhadap Revisi Kurikulum 2013 - Mujahidil Mustaqim (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2017)
Abstract. This article is based on the preliminary findings in the field that prospective teachers or students of practical field experience (PPL) are not comprehensively mastered therevised 2013 curriculum. This is reflected in the following matters: (a) Students of PPL initially and truly learn the essence of the revised curriculum during the PPL and not at the time of micro teaching lectures in the class. (b) Higher education does not provide a full 2013 curriculum concept so that students of PPL assessed having no adequate provisions to implement the revised curriculum. (c) The curriculum is quite often changed in a decade which complicate theteacher’s candicates to understand the essence of curriculum differences from time to time. (d) Students of PPL often confused due to the gaps in understanding the 2013 curriculum whichthey studied theoretically in college compared to the practical in the field (e) other confusion is there are several schools and a number of teachers who have not been entirely accepted the concept of curriculum offered. Thus, this article reveals the following three points: First, the level of understanding of teacher’s candidates to the revised curriculum of 2013 was 69.1%. Second, the level of understanding of teacher’s candidatesin the implementation of the revised curriculum of 2013 amounted to 57.5%. Third, the level of understanding of teacher’s candidatesto the evaluation of revised curriculum amounted to 13.6%. Fourth, the level of understanding of teacher’s candidates torevised curriculum as a whole includes an understanding of planning, implementation, and evaluation is 49.6%.Keywords: Revised Curriculum 2013, Practice Field Experience, Teacher‘s CandicatesAbstrak.Artikel ini didasari atas temuan sementara di lapangan bahwa calon guru atau mahasiswa praktek pengalaman lapangan (PPL) tidak menguasai secara komprehensif revisi kurikulum 2013. Ini tergambar dari hal-hal berikut: (a) Mahasiswa PPL betul-betul baru belajar esensi revisi kurikulum 2013 ketika sudah melakukan PPL bukan pada saat tatap muka perkuliahan terutama micro teaching. (b)Perguruan Tinggi tidak membekali konsep kurikulum 2013 secara penuh sehingga mahasiswa PPL dinilai tidak mempunyai bekal yang cukup untuk mengimplenetasikan revisi kurikulum 2013 di sekolah. (c) Kurikulum yang cukup sering berubah dalam satu dekade menyulitkan calon guru dalam memahami esensi perbedaan kurikulum dari waktu ke waktu. (d) Seringkali mahasiswa PPL mengalami kebingungan karena ada kesenjangan pemahaman kurikulum 2013 yang dipelajari secara teoritis di perguruan tinggi dengan praktis di lapangan (e) Kebingungan lainnya adalah ada beberapa sekolah dan sejumlah guru yang belum sepenuhnya well come dengan konsep kurikulum yang ditawarkan. Dengan demikian, artikel ini mengungkap tiga hal berikut:Pertama, tingkat pemahaman calon guru terhadap revisi kurikulum 2013 adalah sebesar 69,1 %. Kedua, tingkat pemahaman calon guru terhadap implementasi revisi kurikulum 2013 adalah sebesar 57.5 %. Ketiga, tingkat pemahaman calon guru terhadap evaluasi revisi kurikulum 2013 adalah sebesar 13.6 %. Keempat, tingkat pemahaman calon guru terhadap revisi kurikulum 2013 secara keseluruhan meliputi pemahaman perencanaan, implementasi dan evaluasi adalah sebesar 49,6 %.Kata Kunci: Revisi Kurikulum 2013, Praktek Pengalaman Lapangan, Profesionalitas Guru